1991
DOI: 10.1021/tx00020a018
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of L-canavanine and L-canaline in the tobacco budworm, Heliothis virescens [Noctuidae]

Abstract: The metabolism of L-canavanine and L-canaline were investigated in larvae of the tobacco budworm, Heliothis virescens [Noctuidae]. H. virescens larvae were treated with L-[1,2,3,4-14C]canavanine or L-[U-14C]canaline with sufficient cold carrier to provide 5 mg g-1 canavanine or a molar equivalent of canaline (3.81 mg g-1). The preponderant catabolite in both canavanine- and canaline-treated larvae was [14C]homoserine. Other minor metabolites derived from canavanine included [14C]aspartate/asparagine, [14C]glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In contrast, tobacco hornworm larvae, Manduca sexta, maintained on a 2.5 mM canavanine-containing diet develop massive developmental aberrations (1,2). The appreciable natural resistance of H. virescens to this protective allelochemical instigated earlier studies to elucidate the biochemical basis for canavanine tolerance by H. virescens (7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, tobacco hornworm larvae, Manduca sexta, maintained on a 2.5 mM canavanine-containing diet develop massive developmental aberrations (1,2). The appreciable natural resistance of H. virescens to this protective allelochemical instigated earlier studies to elucidate the biochemical basis for canavanine tolerance by H. virescens (7)(8)(9).…”
mentioning
confidence: 99%
“…Administration of L-[guanidinooxy- 14 C]canavanine to fifth instar H. virescens larvae disclosed that [ 14 C]guanidine was the principal in vivo larval radiolabeled canavanine catabolite (9). Subsequent in vivo studies employing L- [1,2,3,4-14 C]canavanine identified L- [1,2,3,4-14 C]homoserine as the preponderant radiolabeled catabolite (9). These studies of radiolabeled metabolite disposition implicated a larval reductase in the detoxification of canavanine via homoserine and guanidine.…”
mentioning
confidence: 99%